Pengaruh Electronic Word Of Mouth (ewom) Terhadap Niat Beli Produk Scarlett Di Shopee - Oktaviani, Amelia; Tantra, Tarandhika (eProceedings of Management, 2024)
In the digital era, electronic word of mouth (e-WOM) has become an important marketing strategy to increaseconsumer buying interest. With more than 212 million Indonesian internet users as of January 2023, the growth of ecommerce platforms is increasing rapidly. The Internet gives consumers more choices according to their preferences,which are now often influenced by e-WOM. Expression of products is now more often done electronically, so e-WOMcan change consumer preferences. This research aims to analyze the influence of e-WOM on consumer buying interestin Scarlett products on Shopee. To understand the impact of e-WOM, this research adopts a model from previousresearch. It is hoped that the results of this research will help Scarlett improve its marketing strategy and provideguidance for MSMEs in the beauty industry in developing their business through e-WOM and Shopee. Research datawas collected from 401 respondents who filled out a Google Form questionnaire with certain criteria, such asIndonesian people who are male and female and buyers of Scarlett products on Shopee. The methodology used isdescriptive quantitative with data collection techniques via Likert scale questionnaires, then processed using SMART - PLS. The research results show that the application of information has a positive and significant influence onpurchasing interest. This model is able to predict interest in purchasing Scarlett products by 90.5%. Apart from that,a significant indirect effect on purchase intention was also found in the structural model. This research is limited tothe beauty business sector and the majority of respondents are women, so the findings cannot be generalized to otherbusiness sectors or various genders. Future research is recommended to consider additional factors that may improvethe model's ability to predict information adoption. In addition, future research can apply this model to other businesssectors or different e-commerce platforms. Keywords-information adoption model, purchase intention, electronic word-of-mouth, Shopee.